European gothic : a spirited exchange, 1760-1960 - Horner, Avril, 1947- (Manchester University Press, 2017)
The book charts the rich process of cross-fertilisation, especially regarding Anglo-French exchanges in the development of the Gothic novel and emphasises the importance of the impact of translation on the development of the Gothic novel. Each chapter offers a fresh way of thinking about Gothic lineages and histories. This work uses a variety of critical perspectives to reassess the work of authors such as Clara Reeve, Sophia Lee, Charlotte Smith, Ann Radcliffe, Matthew Lewis, Charles Maturin, Coleridge, Mary Shelley, Jan Potocki, Balzac, Dostoevesky, Gaston Leroux and Djuna Barnes.
Keywords: Gothic literature -- History and criticism.; Gothic revival (Literature) -- Europe.; European fiction -- History and criticism.; European fiction -- 19th century -- History and criticism.; Roman européen -- 19e siècle -- Histoire et critique.; Roman européen -- Histoire et critique.; Littérature frénétique -- Europe.; Littérature gothique -- Histoire et critique.; 17.86 literary genres, theory of genre.; Literature.; Literature -- History & Criticism.; LITERARY CRITICISM -- General.; LITERARY CRITICISM / General; Gothic revival (Literature); Gothic literature; European fiction; Europe; Gothic novel; Schauerroman; Aufsatzsammlung; Europa; Gothic Revival (letterkunde); Gothic novel.; Griezelromans.; Literature -- History & criticism.; 1800-1899; Electronic books; Criticism, interpretation, etc.